Implementation of Green Accounting in Business Sustainability - Putri, Audyta Prasetyani; Yance, Evy; Hwihanus; Sultoni, Mohammad Hamim; Ahmed, Ishfaq (Shafin: Sharia Finance and Accounting Journal, 2025)
The purpose of this study is to ascertain how green accounting implementation affects the sustainability of businesses. The findings of earlier studies will be examined in order to examine this influence. The meta-analysis method is employed in this study. A meta analysis examines several research findings on related issues. Written research on the application of green accounting in business sustainability, in the form of journal articles selected for their alignment with the research theme, serves as the unit of analysis for this study. With the use of a documentation guide, the researcher is the primary tool in this study. Both quantitative data analysis using percentages and qualitative data analysis using narrative study data from the research findings were employed in the data analysis process. Sample errors were determined by calculating the findings of the meta-analysis. The variance of the population correlation is 0.569, while the sampling error variance is 0.023. A relatively modest percentage of variance, or 4%, is created by sampling error when the variance value of the sample error is compared to the population correlation variance value multiplied by 100%. This percentage shows that sampling error-related error bias is minimal.